Confirmation of B-Cell Epitope of Nucleoprotein of Newcastle Disease Viruses by Dot-ELISA and Peptide ELISA - Pushpa , R.N. Ramani; Kirubaharan, J. John; Koteeswaran, A. (International Journal of Poultry Science, 2012)
A conserved B-cell epitope of nucleoprotein with the amino acid sequence “FLDLMRA” was found to be located in the conserved region between 443GETQFLDLMRAVANS457 of nucleoprotein of all four vaccine viruses used in South India. The conserved region incorporating the epitope 443GETQFLDLMRAVANS457 has been synthesized as a custom peptide. The immunodominance of the epitope was confirmed by dot-ELISA and peptide ELISA. Peptide ELISA developed using the entire conserved region was found to produce a consistent result with HI and Whole Virus Protein (WVP) ELISA. The immunodominance and immunogenicity was identified and confirmed by significant positive correlation (p